2016
DOI: 10.1007/s00107-016-1090-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface properties and solvent-borne coating performance of red oak wood produced by peripheral planing

Abstract: Alexandre Miguel do Nascimentovi AGRADECIMENTOS À Deus pela saúde e força para executar esse trabalho. À minha filha Maria Carolina, por compreender os dias de ausência e me incentivar a cada dia na execução dessa tese.À meus familiares, em especial minha mãe por sempre incentivar a minha caminhada no conhecimento acadêmico e de vida.À Universidade Federal Rural do Rio de Janeiro (UFRRJ) por ter me dado a oportunidade da aquisição de conhecimento.À Universidade Federal do Acre (UFAC) pelo incentivo e confiança… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…The anatomical influence can be reduced with the help of such filters and the roughness profile can be optimised for surface evaluation of the sample [29,30]. Moreover, when analysing deep valleys on the sample surface, the robust Gaussian filter does not produce distortions that maybe formed by other filters [31]. The mean surface roughness (Sa) is the most widely used parameter for describing the variations in surface height and was calculated according to ISO 4287 (1997).…”
Section: (B)mentioning
confidence: 99%
“…The anatomical influence can be reduced with the help of such filters and the roughness profile can be optimised for surface evaluation of the sample [29,30]. Moreover, when analysing deep valleys on the sample surface, the robust Gaussian filter does not produce distortions that maybe formed by other filters [31]. The mean surface roughness (Sa) is the most widely used parameter for describing the variations in surface height and was calculated according to ISO 4287 (1997).…”
Section: (B)mentioning
confidence: 99%
“…Generally, in terms of adherence, small differences were found when comparing the two varnish products. Results of other studies revealed that water-based finishes induced greater surface roughness, increasing the contact area and thus resulting in a better adherence to the wood surface [13,35].…”
Section: Evaluation Of the Coating Propertiesmentioning
confidence: 99%
“…The substrate preparation prior to the varnish application and the coating product present a specific influence on the properties of the final finished product [13]. The wood grain may raise, twist, and lift during the wetting and sanding, which can be reduced with a proper sanding process [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface quality of solid wood products is one of the most important properties infl uencing further manufacturing processes such as fi nishing (coating) or strength of adhesive joint (Kilic et al, 2006; Aguilera and Muñoz, 2011; Ugulino and Hernández, 2016). Nevertheless, determination of surface quality in planing is a complex process depending on the heterogeneous structure of wood species (Belleville et al, 2016;Malkoçoğlu and Özdemir, 2006;Malkoçoğlu, 2007;Sofuoğlu and Kurtoğlu, 2015), kinematics of the cutting process (Hernández and•Cool, 2008;Gottlöber et al, 2015), and machining conditions (Jokerst and Stewart, 1976;Malkoçoğlu, 2007;Minami and Nishio, 2015;Stewart, 1980;Ugulino and Hernández, 2016).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%